The Directive 2014/104/UE on Antitrust Damages Actions: A critical review - Vanessa JIMÉNEZ SERRANÍA (Ars Iuris Salmanticensis, 2016)
In November 2014, the Directive on antitrust damages actions became law in the EU.This Directive constitutes, undoubtedly, a major step forward in strengthening private enforcement. Indeed, it attempts to facilitate antitrust damages claims and to ensure a full compensation for the victims. On the other hand, the implementation of this Directive will require significant adjustments in the legal systems of most of the member states, including Spain. The purpose of this paper is to examine the main provisions of the Directive from a critical point of view. To that end, their compatibility with Spanish law will be assessed and their consistency with the necessary balance between public and private enforcements will be investigated.